Identification and characterization of the proteins bound by specific phage-displayed recombinant antibodies (scFv) obtained against Brazil nut and almond extracts - de la Cruz, Silvia; Madrid, Raquel; García, Aina; Alcocer, Marcos; Martín, Rosario; González, Isabel; García, Teresa (Wiley, 2017)
BACKGROUND